2006
DOI: 10.1007/s11104-006-6249-1
|View full text |Cite
|
Sign up to set email alerts
|

Coupling N Cycling and N Productivity in Relation to Seasonal Stress in Quercus Pyrenaica Willd. Saplings

Abstract: The N economy of saplings of the Mediterranean Quercus pyrenaica Willd. species was analysed at wholeplant level. The amount and timing of N cycling were determined by strong seasonality in N productivity, which peaked in late spring. Most leaf N was allocated to a main first flush of leaves in early spring, and a minor second flush during early summer or autumn. After peak of N productivity, the allocation of biomass production and N resources was mainly switched to lignotuber and coarse roots. Q. pyrenaica d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 57 publications
1
25
1
Order By: Relevance
“…This could explain the fact that the total soil N found in this study was higher than the levels reported by Silla & Escudero (2006) and Turrión et al (2009) in Q. pyrenaica forests developed over granites. In the case of Q. rotundifolia and Q. suber, total soil N contents were between the range obtained by Canadell and Vilá (1992) for Q. ilex forests studied in Spain & Otieno et al (2011) for Q. suber forests in Southern Portugal.…”
Section: Soil Biomass In Quercus Species 431contrasting
confidence: 73%
“…This could explain the fact that the total soil N found in this study was higher than the levels reported by Silla & Escudero (2006) and Turrión et al (2009) in Q. pyrenaica forests developed over granites. In the case of Q. rotundifolia and Q. suber, total soil N contents were between the range obtained by Canadell and Vilá (1992) for Q. ilex forests studied in Spain & Otieno et al (2011) for Q. suber forests in Southern Portugal.…”
Section: Soil Biomass In Quercus Species 431contrasting
confidence: 73%
“…We chose the plants randomly, although those severely damaged or visually infested with Malacosoma neustrium caterpillars were excluded. Previous work had shown that the generalist M. neutrium was the main herbivore species of Q. pyrenaica at the study site (Silla and Escudero 2006). Although the population density of M. neustrium was low during 2003, this species is a tent caterpillar exhibiting gregarious behaviour and some individual plants were severely defoliated.…”
Section: Experimental Designmentioning
confidence: 81%
“…Thus, around &13 and &26% of the leaf area in the selected stem was removed in the low and high treatments, respectively. These treatments intended to represent the frequent but low-moderate damage (1-20% of leaf area loss at whole plant-level) and the scarce but intense damage (21-60%) that was found previously in saplings of this study area (Silla and Escudero 2006). However, we mimicked the scale of damage only at stem level, as we want to study if the responses to damage were induced locally or at whole plant-level (Meyer and Whitlow 1992;Retuerto et al 2004).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This species is well adapted to surviving summer water deficits while maintaining photosynthetic production (Gallego et al, 1994;Rico et al, 1996). Q. pyrenaica has been poorly studied in relation to other Mediterranean Quercus species (Silla and Escudero, 2006).…”
Section: Introductionmentioning
confidence: 99%